2014
DOI: 10.1002/jor.22764
|View full text |Cite
|
Sign up to set email alerts
|

Articular contact kinematics of the knee before and after a cruciate retaining total knee arthroplasty

Abstract: Accurate knowledge of tibiofemoral articular contact kinematics of the knee after total knee arthroplasty (TKA) is important for understanding the intrinsic knee biomechanics and improving the longevity of the components. The objective of this study was to compare the in vivo articular contact kinematics of the knees with end-stage medial osteoarthritis (OA) during a weightbearing, single leg lunge activity before and after a posterior cruciate retaining TKA (CR-TKA) using a dual fluoroscopic imaging technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 50 publications
(153 reference statements)
2
17
0
Order By: Relevance
“…In these studies, the imaging equipment remained fixed relative to the ground while subjects ambulated on a treadmill. Thus, even for relatively slow walking speeds, it has been possible to analyze only a portion of the stride cycle because the joint invariably strays beyond the capture volume of the X‐ray imaging device …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, the imaging equipment remained fixed relative to the ground while subjects ambulated on a treadmill. Thus, even for relatively slow walking speeds, it has been possible to analyze only a portion of the stride cycle because the joint invariably strays beyond the capture volume of the X‐ray imaging device …”
mentioning
confidence: 99%
“…Thus, even for relatively slow walking speeds, it has been possible to analyze only a portion of the stride cycle because the joint invariably strays beyond the capture volume of the X-ray imaging device. [8][9][10][11][12] X-ray fluoroscopy also has been used to measure the locations of the tibiofemoral joint contact centers during weight-bearing activities such as lunging. 13,14 The results indicate that the contact center moves further in the lateral compartment than in the medial compartment, suggesting that the femur pivots about the medial tibial condyle and that axial rotation of the tibia is coupled to the knee flexion angle.…”
mentioning
confidence: 99%
“…[13][14][15][16][17] Some have shown that gap balancing techniques result in less kinematic variation, while others have shown how small variations in transverse plane positioning of implants may affect the final kinematic profile of a TKA. [13][14][15][16][17] Keeping in mind how these many variables may play a role in TKA kinematics during demanding activities, it may be beneficial for implant designs to be more forgiving and less constraining in the transverse plane. Others may suggest that it means more accurate surgical techniques should be employed to assure proper rotation and a more functional means of implant positioning needs to be utilized during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last 10 years, several studies analyzed 3D joint space of the knee and deduced articular contact kinematics during various weight-bearing activities (Li et al 2015). Joint space and articular contact kinematics provide relevant data on how the intrinsic biomechanics of the knee is altered after a disease or a surgical procedure, such as knee osteoarthritis (OA) or total knee arthroplasty (Li et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Joint space and articular contact kinematics provide relevant data on how the intrinsic biomechanics of the knee is altered after a disease or a surgical procedure, such as knee osteoarthritis (OA) or total knee arthroplasty (Li et al 2015).…”
Section: Introductionmentioning
confidence: 99%